Réponses

  • Omnes
  • Modérateur confirmé
2014-03-16T16:44:54+01:00
Salut,
A = 4(x+3)
A = 4x + 12

B = 2(x+7)
B = 2x + 14

C = 3(2x + 7)
C = 6x + 21

D = 4(3x + 1)
D = 12x + 4

E = 7(3x - 4)
E = 21x - 28

F = 5(2x -3)
F = 10x - 15

G = 4(-2x + 3)
F = -8x + 12

H = 3(-3x + 7)
H = -9x + 21

I = 6(-3x -7)
I = -18x - 42

J = 5(-2x -3)
J = -10x - 15

Développer et réduire :

K = (-3x + 1 )(-5x + 4)
K = 15x² - 12x - 5x + 4
K = 15x² - 17x + 4

L = (-2x - 1)(-3x² +7)
L = -6x^3 -14x + 3x² - 7
L = -6x^6 + 3x² - 14x - 7

M = (-5x - 2x²)(-4x - 3x^3)
M = 20x² + 3x^4 + 8x^3 + 6x^5

N =(-9x²)(-6x² + 7)
N = 54x^4 - 63x²

O = (3-5x)(4x^3 - 2x^3)
O = (3-5x)(2x^3)
O = 6x^3 - 10x^4

Bonne journée !
2014-03-16T16:48:50+01:00
A=4(x+3)=4xx+4x3=4x+12
B=2(x+7)=2xx+2x7=2x+14
C=3(2x+7)=3x2x+3x7=6x+21
D=4(3x+1)=4x3x+4x1=12x+4
E=7(3x-4)=7x3x-7x4=21x-28
F=5(2x-3)=5x2x-5x3=10x-15
G=4(-2x+3)=4x(-2x)+4x3= -8x+12
H=3(-3x+7)=3x(-3x)+3x7= -9x+21
I=6(-3x-7)=6x(-3x)-6x7= -18x-42
J=5(-2x-3)=5x(-2x)-5x3= -10x-15